2004
DOI: 10.1111/j.1440-1843.2003.00518.x
|View full text |Cite
|
Sign up to set email alerts
|

Pleural complications of pulmonary hydatid disease

Abstract: Pleural lesions associated with pulmonary hydatid disease are rare and have a variable radiographic appearance. In regions in which echinococcal disease is endemic, a high level of clinical suspicion is necessary for diagnosis and appropriate management of this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 17 publications
0
23
1
1
Order By: Relevance
“…Mean age was found 11.29 + 2.44 (8)(9)(10)(11)(12)(13)(14)(15). Ten cases (58.8%) were residing in urban areas whereas 7 (41.1%) cases came from rural areas of Anatolia.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Mean age was found 11.29 + 2.44 (8)(9)(10)(11)(12)(13)(14)(15). Ten cases (58.8%) were residing in urban areas whereas 7 (41.1%) cases came from rural areas of Anatolia.…”
Section: Resultsmentioning
confidence: 93%
“…9,11,12,14 We found higher incidence of liver lesions more frequent than other studies (47%) and there was also an additional splenic cyst in one case (5.8%). 15 The intradermal Casoni test is well known human basophile degranulation test, performed with hydatid antigens. It gives good, helpful results especially with pulmonary localization and a negative antibody assay.…”
Section: Discussionmentioning
confidence: 99%
“…Intrathoracic but extrapleural hydatid cysts are still rarer and can be located in the fissures, pleural cavity, chest wall, mediastinum, myocardium, and diaphragm. Though daughter cysts in pleura and pleural complications of primary pulmonary hydatid disease have been reported, primary extra-pulmonary hydatids are extremely rare [1,2]. Thameur H et al reported an incidence of 5.62% of extrapulmonary hydatidosis in their review of 1,619 cases of thoracic hydatidosis [7].…”
Section: Discussionmentioning
confidence: 99%
“…Liver cysts are the most common form of human eichinococcosis. While lungs are the second most common site of lodgment, thoracic hydatidosis that are extrapulmonary are rare [1,2]. Extrapulmonary hydatid cysts are still rarer and can be located in the fissures, pleural cavity, chest wall, mediastinum, myocardium, and diaphragm.…”
Section: Introductionmentioning
confidence: 99%
“…Intrathoracic but extrapleural hydatid cysts are still rarer and can be located in the fissures, pleural cavity, chest wall, mediastinum, myocardium, and diaphragm. Though daughter cysts in pleura and pleural complications of primary pulmonary hydatid disease have been reported, primary extra-pulmonary hydatids are extremely rare [5,6] . The route of pulmonary infestation can be Intestinal, lymphatics, venal-venous anastomosis in the liver and the space of Retzius.The clinical features of cystic hydatidosis are highly variable and depend on the size, number of cyst, location in the thorax, and their interaction with the surrounding organs.…”
Section: Discussionmentioning
confidence: 99%